Operational Transparency as a Service Design: An Investigation on Labor/Effort Observation Effect - Hwang, Eun Min (Min); Lee, Seonjeong (Ally); Legendre, Tiffany S. (Journal of hospitality & tourism research (Washington, D.C.), 2024)
Increasing operational transparency offers customers the opportunity to observe the labor and efforts of service staff in the service production and delivery process. This study explores the impact of service design on customers’ affective, cognitive, and behavioral responses. This study first investigates the effects of operational transparency on customers’ brand evaluation and purchase intention through gratitude (affective) and perceived value (cognitive). This study also explores the moderating role of relationship norms in the proposed relationships. Based on two between-subjects experiments, Study 1 identifies the serial mediating role of customer gratitude and perceived value on the relationship between operational transparency and customers’ brand evaluation and their purchase intention. The results of Study 2 demonstrate that the Study 1 discovery only lasts when the exchange relationship norm prevails in a customer-service brand relationship. The theoretical and managerial implications of operational transparency in enhancing customer service experience are discussed.